The Chinese aesthetic tradition - Li, Zehou (University of Hawaiʻi Press, 2010)
Touching on all aspects of artistic activity, Li demonstrates the fundamental role of aesthetics in the development of the cultural & psychological structures in Chinese culture that define 'humanity'.
Keywords: Aesthetics, Chinese -- History.; Esthétique chinoise -- Histoire.; PHILOSOPHY -- Aesthetics.; PHILOSOPHY -- Eastern.; Aesthetics, Chinese; Ästhetik; China; Geschichte.; Electronic books.; History